Resources wages in the United States grow only slightly, while China and India see double-digit increases. - Costlow, T. (IEEE spectrum)
This paper discusses the current state of wages earned by engineers in the US. In general, US engineers are seeing modest salary gains, and wage freezes are pretty much a thing of the past. Though the US economy is said to be picking up, that hasn't necessarily translated into robust hiring or salary increases. While US engineers still make more compared to their European counterparts, engineers in low-wage countries such as China and India are enjoying double-digit salary increases.